The Influence of Product Quality and Price on The Purchase Decision of Fukumi Porang Rice in Bandar Lampung - Sofiyatul Azkiyah; Aida Sari (Green Economics: International Journal of Islamic and Economic Education, 2025)
This research aims to examine how product quality and price influence the purchasing decisions of consumers buying Fukumi brand porang rice in Bandar Lampung City. As a healthier rice alternative, Fukumi porang rice has become popular among individuals who are health-conscious, particularly those on diets or managing diabetes. A quantitative method was applied, using surveys distributed to 150 buyers of Fukumi rice. The data were analyzed using multiple linear regression. The findings reveal that both product quality and price have a significant impact on purchasing decisions. The regression analysis shows that product quality accounts for 54.1%, while price accounts for 57% of the decision-making process. An Adjusted R² of 0.567 indicates that 56.7% of the variation in purchase decisions is explained by these two factors, with the remaining 43.3% influenced by other variables not included in this study. These results emphasize the need for businesses to consistently deliver high product quality and set prices that reflect customer value to stay competitive.